2006
DOI: 10.1080/10473289.2006.10464449
|View full text |Cite
|
Sign up to set email alerts
|

The Influences of Ambient Particle Composition and Size on Particle Infiltration in Los Angeles, CA, Residences

Abstract: Particle infiltration is a key determinant of the indoor concentrations of ambient particles. Few studies have examined the influence of particle composition on infiltration, particularly in areas with high concentrations of volatile particles, such as ammonium nitrate (NH 4 NO 3 ). A comprehensive indoor monitoring study was conducted in 17 Los Angeles-area homes. As part of this study, indoor/outdoor concentration ratios during overnight (nonindoor source) periods were used to estimate the fraction of ambien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
60
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(67 citation statements)
references
References 29 publications
6
60
1
Order By: Relevance
“…F inf is typically highest for nonvolatile species such as EC. 27,28 To estimate F inf for OC, EC, PM 2.5 , and PN, two different techniques were used: an analysis of the indoor/outdoor concentration ratios and the recursive model (RM) developed by Allen et al 29 In the first approach, hourly indoor/outdoor ratios (I/O) for each particulate species were determined at times when no indoor particle sources, such as cooking or cleaning, were likely to be present (i.e., only I/O ratios Յ1 were considered). Daily F inf estimates were then obtained by averaging these segregated hourly I/O ratios.…”
Section: Discussionmentioning
confidence: 99%
“…F inf is typically highest for nonvolatile species such as EC. 27,28 To estimate F inf for OC, EC, PM 2.5 , and PN, two different techniques were used: an analysis of the indoor/outdoor concentration ratios and the recursive model (RM) developed by Allen et al 29 In the first approach, hourly indoor/outdoor ratios (I/O) for each particulate species were determined at times when no indoor particle sources, such as cooking or cleaning, were likely to be present (i.e., only I/O ratios Յ1 were considered). Daily F inf estimates were then obtained by averaging these segregated hourly I/O ratios.…”
Section: Discussionmentioning
confidence: 99%
“…At an AER of 0.45 h À1 , ambient particulate nitrate indoors was only 12% of its outdoor concentration; in contrast, F was 0.67 Outdoor and indoor concentrations of ambient PM 2.5 and the fraction of outdoor PM 2.5 that penetrates and persists indoors (F) for the scenarios described in Figure 1 and (Figure 3) are in agreement with the range of F values reported by several studies (F ¼ 0.32--0.8). 36 Sarnat et al 42 and Lunden et al 43 The model showed little sensitivity to changes in k dep with variations in species-specific size distributions across season and location; it was more sensitive to changes in P filter . The overall F value for scenario (a: NE composition) did not change when k dep values fit based on the Fresno species-specific size distributions were used rather than the New York City size distributions.…”
Section: Main Analysismentioning
confidence: 99%
“…In general, d S increases both indoors and outdoors in the evening as the temperature drops, which, as argued earlier, is probably due to condensational growth of the particles at that time. However, the mean indoor diameter is always slightly lower than the outdoor (except between 3:00-5:00), which may be due to some particle evaporation as the aerosol is transported in the warmer indoor environment (Kuhn et al 2005;Lunden et al 2003;Sarnat et al 2006). For example, particulate compounds such as ammonium nitrate and organic species, which may account for 35-60% of outdoor PM 2.5 mass in the Los Angeles basin (Kim et al 2000;Tolocka et al 2001), volatilize as they entrain indoors (Lunden et al 2003).…”
Section: Mean Surface Diametermentioning
confidence: 99%